Abraham model correlations for solute transfer into benzyl alcohol from both water and the gas phase. (2nd January 2020) - Fischer, Rachel; Jodray, Megan; Qian, Ellen; Wang, Lainey; Lee, Grace; Yue, David; Che, Melanie; Liu, Yuqing; Acree, William E.; Abraham, Michael H.
ABSTRACT: Experimental solubilities have been determined for anthracene, benzil, 2-chloroanthraquinone, 9-fluorenone, 2-hydroxybenzoic acid, 2-methoxybenzoic acid, 2-methylbenzoic acid, 3-methylbenzoic acid, phenothiazine, pyrene, and thioxanthen-9-one dissolved in benzyl alcohol at 298.15 K. The measured solubility data, combined with previously published activity coefficient and solubility data, are used to determine Abraham model correlations for solute transfer to benzyl alcohol from both water and from the gas phase. The derived Abraham model correlations were found to back-calculate the experimental partition coefficients and solubility ratios to within 0.14 log units (or less).